2020
DOI: 10.1113/ep088450
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to investigate the associations of urinary concentrations of NO, ATP and derivatives with overactive bladder symptom severity

Abstract: Overactive bladder (OAB) is a highly prevalent symptom complex characterized by symptoms of urinary urgency and increased frequency and waking to void (nocturia), with or without urge incontinence and in the absence of proven infection or other obvious pathology. The underlying pathophysiology of idiopathic OAB is not clearly known, and the existence of several phenotypes has been proposed. Current diagnostic approaches are based on discordant measures, suffer from subjectivity and are incapable of detecting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Previous studies have suggested that ATP might be degraded at the luminal surface of the bladder mucosa. Thus, bladder umbrella cells appear to express ATP-metabolizing enzymes [ 66 , 67 ] and ATP metabolites have been found in the lumen of mouse and monkey bladders [ 3 , 4 ] and in human urine samples [ 23 , 68 ]. In contrast, studies in rabbit mucosa sheets mounted in Ussing chambers failed to detect hydrolysis of exogenous ATP added to the mucosal chamber [ 8 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that ATP might be degraded at the luminal surface of the bladder mucosa. Thus, bladder umbrella cells appear to express ATP-metabolizing enzymes [ 66 , 67 ] and ATP metabolites have been found in the lumen of mouse and monkey bladders [ 3 , 4 ] and in human urine samples [ 23 , 68 ]. In contrast, studies in rabbit mucosa sheets mounted in Ussing chambers failed to detect hydrolysis of exogenous ATP added to the mucosal chamber [ 8 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, decreased intravesical ATP has been found in patients with refractory detrusor overactivity and bacteriuria [ 19 ] and in patients with underactive bladder syndrome [ 20 ]. Such observations have increasingly suggested ATP as a relevant biomarker of bladder dysfunctions [ 11 , 12 , 21 , 22 , 23 , 24 ]. It was recently alluded that ATP might be a better urinary marker than acetylcholine and prostaglandin E2, as the majority of ATP in urine is thought to originate in the lower urinary tract (LUT), whereas the other two substances may also arise from extraction from the plasma into the urine in the kidneys [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Previous studies demonstrated that the levels of different proteins and /or metabolites are increased in patients with OAB as compared to controls and they may also correlate with the severity of OAB symptoms. 6,7 To date, evidence has shown that urinary proteins such as nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) are increased in patients with OAB, but also in a number of conditions including bladder outlet obstruction (BOO) and interstitial cystitis. [8][9][10][11][12] However, knowledge gaps regarding the causality persist and the clinical utility of these observations is not yet quantified.…”
Section: Introductionmentioning
confidence: 99%